2016
DOI: 10.1055/s-0035-1568145
|View full text |Cite
|
Sign up to set email alerts
|

Complications Following Anorectal Surgery

Abstract: Anorectal pathology is prevalent throughout the world, with most anorectal complaints being transient and without the need for formal medical evaluation. For those that do require surgical intervention for their anorectal pathology, the surgery can usually be done safely in the outpatient setting with minimal morbidity. However, no intervention is without risk, and complications frequently arise after anorectal surgery, with rates upward of 50% in some studies. 1 The purpose of this chapter is to review the sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
48
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 55 publications
(86 reference statements)
3
48
0
5
Order By: Relevance
“…Early postoperative hemorrhage is defined as immediate bleeding which happens within the early postoperative period from 24 to 48 hours and is likely related to the loss of control of the vascular pedicle. Delayed bleeding is defined as a hemorrhage reported up to 2 weeks postoperatively, and is more often related to infection or local trauma [16]. Considering the bleeding rates in the present study, it was in agreement with the literature even though the definition of hemorrhage differs.…”
Section: Discussionsupporting
confidence: 89%
“…Early postoperative hemorrhage is defined as immediate bleeding which happens within the early postoperative period from 24 to 48 hours and is likely related to the loss of control of the vascular pedicle. Delayed bleeding is defined as a hemorrhage reported up to 2 weeks postoperatively, and is more often related to infection or local trauma [16]. Considering the bleeding rates in the present study, it was in agreement with the literature even though the definition of hemorrhage differs.…”
Section: Discussionsupporting
confidence: 89%
“…For conventional hemor rhoidectomy (Milligan-Morgan and Ferguson) and bipolar energy device hemorrhoidectomy (LigaSure), rates of bleeding between 0 and 49% have been reported. Clinically significant bleeding has been reported in 0.3-6% of patients, with an average of around 2%, and need of reintervention between 1-2%, without a significant difference in rates of bleeding between the procedures [121,182,183].…”
Section: Bleeding: Fewer People Have Postoperative Bleeding After Thdmentioning
confidence: 99%
“…Bleeding after RBL normally occurs between 5 and 14 days after treatment, probably due to the sloughing of the ligated hemorrhoids [182].…”
Section: Bleeding: Fewer People Have Postoperative Bleeding After Thdmentioning
confidence: 99%
See 1 more Smart Citation
“…The treatment of endstage cancer pain is challenging due to the side effects of opioids and its nature in a way to require interventional approaches. It has been reported that persistent pain may develop at a rate of 1.5-3.5% after the transanal rectal resection (12). The underlying cause is primarily taken into consideration in terms of the treatment of chronic anorectal pain; unfortunately, there is no consensus concerning the treatment process (13).…”
Section: Discussionmentioning
confidence: 99%